Bond wire lift-off monitoring based on intersection point movement characteristic in IGBT module. (October 2021) - Du, Mingxing; Xin, Jinlei; Wang, Hongbin; Ouyang, Ziwei; Wei, Kexin
Abstract: Condition monitoring (CM) the insulated-gate bipolar transistor (IGBT) module is of vital significance to improve the reliability of power electronics system. Collector–emitter on-state voltage V C E, O N is a frequently employed failure precursor to identify the bond wire aging. In this paper, a method of separating V C E, O N is proposed to monitor the bond wire lift-off of IGBT module. Firstly, based on the circuit structure of IGBT module, the V C E, O N is divided into voltage drop across IGBT chip V C h i p and voltage drop across bond wire V B W . Secondly, the working principle of IGBT chip is investigated, and the calculation method of voltage drop across P-i-N diode V P i N is proposed. Finally, the V C h i p is analyzed, and information provided by collector current I C at the I C – V C h i p curve intersection point that is not affected by solder layer fatigue is adopted to monitor the lift-off degree of bond wire. The feasibility of the above methods is verified by theory and experiment.